Rancang Bangun Aplikasi Penggajian Pada PT Matra Unikatama - Andre Aulia; Pantjawati Sudarmaningtyas; Ignatius Adrian Mastan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT Matra Unikatama (MU) is a private company engaged in oil drilling contractor. Located in the city of Sidoarjo, PT MU has 88 office staff and 301 laborers. At present, the presence has been using the presence of fingerprint, the current process employee salary calculation that each day the personnel to retrieve data on the presence of employees previously recorded in the fingerprint machine. The presence of data taken using a flash and the data is read using software presensi fingerprint machine. Presence data is then printed to be checked one by one in order to know the employees who are late and not come to work. After the recording process is done daily presence, the personnel presence to match your data with a doctor's note or a special permit approved by the head of the employee. The problem it self is the calculation error (1), calculation of salaries with long time (2), and fraud (3). Based on the problems that occur in the process of calculating the salaries of employees of PT MU, the authors provide a solution for build employee payroll application.